Great Expectations: The Importance of Procedural Justice and Parenting for Perceptions of Success Among Youth on Probation - Fine, Adam D. (Criminal justice and behavior, 2024)
Juvenile probation can be a critical inflection point. As such, researchers, policymakers, and practitioners are interested in enhancing youths’ success on probation, especially pertaining to reducing recidivism and promoting their success in education and employment. Informed by the risk–need–responsivity framework, the present study examined how theoretically derived familial/peer (e.g., social bonds, parental monitoring), societal/community (e.g., labeling theory), and individual-level (e.g., impulsivity, procedural justice) factors were associated with youths’ expectations for success on probation as well as more general life course outcomes. Within samples of youth starting probation (N = 301) and 6 months into probation (N = 253), we combined cross-sectional data from the jurisdiction’s risk/needs tool with a self-reported survey from youth. Youths’ perceptions of parental monitoring and procedural justice were consistently associated with their self-expectations for completing probation. However, for more general life course success, only perceptions of parental monitoring promoted self-expectations. Implications for theory, policy, and practice are discussed.